(untitled) (Pedagogical Horizons, 2021)
In order to address societal challenges in a politically educative way, an offensive, emancipatory understanding of political education is needed that is distinct from an understanding that is focused on prevention. Political education is considered a free space in which all people can become politically capable of acting through education. In order to enable people to participate in politics in an inclusive way, it is necessary to open up spaces of experience for political participation. The goal is to make the practice of collective decisions under conditions of dissent and political action experienceable and reflectable. Political education in schools can only provide these spaces to a limited extent, which is why cooperation with actors in extracurricular political education should be sought. The results of research on a project of political education using a qualitative setting in the tradition of reconstructive social research show that political education that enables real political participation can lead to empowering political experiences. Political participation is then considered a goal and a space of education and experience in the sense of experimental action in which educational processes are initiated.